Transforming Industry Through Hydraulic Solutions, Enhancing Productivity: Mengubah Industri Melalui Solusi Hidraulik, Meningkatkan Produktivitas - Sari, Ghulam Muhammad Abdu; Firdaus, Rachmat (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the workings of such systems in Indonesia, focusing on the flow and pressurization of oil from reservoirs through pumps to working cylinders. Hydraulic systems are crucial in transforming oil fluid pressure into mechanical work, particularly in injection molding machines. Findings indicate that the pump's ability to convert and transmit mechanical energy effectively is pivotal in enhancing machine efficiency. These insights highlight potential areas for improvement in system design and operation, suggesting that optimizing filtration and pressurization could significantly boost industrial productivity and sustainability. Highlights: Hydraulic systems in Indonesia studied for oil flow and pressurization. Pump efficiency crucial for enhancing machine productivity. Optimization of filtration and pressurization can boost industrial sustainability. Keywords: Hydraulic System, Injection Molding Machine, System Works